Republic of Belarus : Technical Assistance Report-Monetary Policy Modeling. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
This Technical Assistance (TA) report on the Republic of Belarus focuses on various aspects of monetary policy modeling. This TA mission was the fifth from series of quarterly IMF TA missions focused on the forecasting and analysis system capacity building. It was mainly aimed to simulate initial conditions and compile a quarterly projection model (QPM)-based forecast scenario as a part of a practical forecasting round at the National Bank of the Republic of Belarus (NBRB) in March. Moreover, the mission worked with the modeling team to deepen its understanding of the QPM's role in policy decision making and in internal communication. Adopting Inflation Targeting and increasing monetary policy effectiveness would require broad-based reforms as compressively outlined in the developed Road Map for Transitioning to Inflation Targeting. This medium-term TA project aims to primarily help the NBRB with medium-term inflation forecasting and policy analysis and related tools to effectively support policy making. The project composed of series of TA and training missions particularly focused on the preparation of forecasts and policy analyses, the medium-term forecasting and policy analysis model, and presentations of the forecasts and policy analysis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet